Translation and validation of the WHO-5 General well-being index into native language Quechua of the Peruvian South - Carranza Esteban, Renzo Felipe (2023)
To translate and validate the WHO-5 General Well-being Index for the people of the Peruvian South, a cross-sectional instrumental study was carried out with the voluntary participation of 186 people of both sexes between the ages of 18 and 65 years (M = 29.67 years old; SD = 10.94) living in the south region of Peru. The validity evidence was assessed based on the content using Aiken’s coefficient V according to the internal structure through a confirmatory factor analysis, and reliability was calculated through Cronbach’s alpha coefficient. The expert judgment was favorable for all items (V > 0.70). The unidimensional structure of the scale was confirmed (χ2 = 10.86, df = 5, p = 0.05; RMR = 0.020; GFI = 0.980; CFI = 0.990; TLI = 0.980 y RMSEA = 0.080), and it presents a suitable reliability range (α = > 0.75). This shows that the WHO